KERAGAMAN GENETIK VARIETAS PADI japonica DAN indica BERDASARKAN MARKA DNA TERKAIT MUTU RASA - Puji Lestari; Reflinur Reflinur; Dody Dwi Handoko; Mastur Mastur (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
PCR-based markers and evaluation of physicochemical properties should be addressed for the improvement of rice varieties with good eating dan eating quality (EQ). This study aimed to examine the genetic diversity of rice varieties based on DNA markers related to physicochemical properties determining EQ. A total of 46 rice varieties consisting of 22 japonica varieties and 24 indica varieties were examined using 43 PCR-based markers. The results showed that polymorphic information content (PIC) ranged from 0.04 to 0.38, in support of genetic diversity indices which ranged from 0.04 to 0.50 across total markers. Pairwise genetic similarity matrix ranged from 0.40 to 0.98 with the closest genetic distance was observed between two japonica varieties (Dongjin and Hwaseong) and the most distant one was between japonica and indica (Onnuri/Manmi with Cigeulis/Fatmawati). The unweighted neighbor-joining tree clustered the rice varieties into two major clades, indica and japonica, and subsequent subclades were differentiating according to the individual genetic background. The genetic diversity of rice from different subspecies and DNA markers for EQ can effectively be utilized for basic information and marker-assisted selection (MAS) for the development of improved varieties with good EQ in rice breeding program.